Utilizing past and present mouse systems to engineer more relevant pancreatic cancer models - DeCant, Brian T.; Principe, Daniel R.; Guerra, Carmen; Pasca di Magliano, Marina; Grippo, Paul J. (Frontiers in Physiology, 2014)
The study of pancreatic cancer has prompted the development of numerous mouse models that aim to recapitulate the phenotypic and mechanistic features of this deadly malignancy. This review accomplishes two tasks. First, it provides an overview of the models that have been used as representations of both the neoplastic and carcinoma phenotypes. Second, it presents new modeling schemes that ultimately will serve to more faithfully capture the temporal and spatial progression of the human disease, providing platforms for improved understanding of the role of non-epithelial compartments in disease etiology as well as evaluating therapeutic approaches.